The contingent effects of political strategies on firm performance: A political network perspective. (7th June 2018) - Yan, Jackie Zheng; Chang, Sea‐Jin
Abstract : Research Summary: We examine the performance impact of corporate political strategies by analyzing the relationships among firms and various government institutions. While a firm's political connections to a focal government with decision‐making authority enhance performance, connections to a rival government competing with the focal government harm performance, particularly when the rivalry is intense. Firms can neutralize the negative effect from this political rivalry by using direct or indirect connections to a constraining government with power over the focal government. We find support for our conjectures based on an analysis of interactions among Chinese steel firms and the central and provincial governments in acquisition decisions during the industry's consolidation period of 1999–2010. Managerial Summary : Firms invest in political capital in order to influence public policies in their favor. However, the government is a not a monolithic entity and the relationships among various government institutions can alter and even reverse the effects of a firm's political strategy. This research shows that a firm's political connections can be both an asset and a liability. That is, although firms benefit from their connections to governments with decision‐making authority, they can be caught in the crossfire when there is a rivalry between governments. Furthermore, our research suggests that firms can cope with the negative impact from political rivalry by taking advantage of the structural relationships within the political system and influencing governments that have constraining power.